Mechanomics Approaches to Understand Cell Behavior in Context of Tissue Neogenesis, During Prenatal Development and Postnatal Healing - Putra, Vina D. L.; Song, Min Jae; McBride-Gagyi, Sarah; Chang, Hana; Poole, Kate; Whan, Renee; Dean, David; Sansalone, Vittorio; Knothe Tate, Melissa L. (Frontiers in Cell and Developmental Biology, 2020)
Mechanomics is a burgeoning field studying mechanical modulation of stem cell behavior. Analogous to mechanical testing of a living material as it adapts and evolves, mapping of the mechanome (the mechanics equivalent of mapping the genome) necessitates the development of new tools and approaches incorporating physics, principles of mechanics and materials, as well as cell biology and emergent genesis of tissues via structural protein transcription. Here we present two complementary approaches to study mechanobiology and mechanoadaptation of live stem cells. First, we developed and tested tools to enable quantitative study of primary human mesenchymal stem cell motility in model EMT (Epithelial-Mesenchymal-Transition) constructs in a three-dimensional, in vitro cell culture model. In parallel, live imaging methods were developed to track simultaneously dynamic cytoskeletal mechanoadaptation of actin and tubulin in adherent cells from a model embryonic murine mesenchymal stem cell line and a neuroblastoma cell line. This model system enables study of emergent structural mechanoadaptation of the cell's own cytoskeletal machinery while tracking lineage commitment using phenotypic (quantitative morphology measures) and genotypic (e.g. rtPCR) methods. These tools are expected to facilitate the mapping of the mechanome and incipient mechanistic understanding of stem cell mechanobiology, from the cellular to the tissue length scale.